2019
DOI: 10.1093/cercor/bhz045
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal Circuits Encode the Subjective Value of Perceived Control

Abstract: The ability to perceive and exercise control over an outcome is both desirable and beneficial to our well-being. It has been shown that animals and humans alike exhibit behavioral bias towards seeking control and that such bias recruits the ventromedial prefrontal cortex (vmPFC) and striatum. Yet, this bias remains to be quantitatively captured and studied neurally. Here, we employed a behavioral task to measure the preference for control and characterize its neural underpinnings. Participants made a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 94 publications
7
41
0
Order By: Relevance
“…7) and were also more willing to forgo money in order to play the HC task (Spearman's rho = 0.29, one-sided p = 0.029; for POE this effect was not significant after correcting for multiple comparisons; Spearman's rho = −0.18, one-sided p = 0.106; all p-values FDR-corrected). In line with the previous literature on perceived control and task preferences 3,55 , we also observed that people who experienced stronger differences in control beliefs (HC-MC) more strongly preferred the HC task. Participants experiencing stronger control were more likely to select the HC task in case of equal offers (Spearman's rho = 0.28, one-sided p = 0.048), were willing to forgo money in order to play the HC task (Spearman's rho = 0.26, one-sided p = 0.048), and showed shifts in the POE so that MC offers needed to be larger in order to achieve similar probabilities of selecting HC and MC (Spearman's rho = −0.24, one-sided p = 0.048, all p-values FDR-corrected; see Supplementary Table 7).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…7) and were also more willing to forgo money in order to play the HC task (Spearman's rho = 0.29, one-sided p = 0.029; for POE this effect was not significant after correcting for multiple comparisons; Spearman's rho = −0.18, one-sided p = 0.106; all p-values FDR-corrected). In line with the previous literature on perceived control and task preferences 3,55 , we also observed that people who experienced stronger differences in control beliefs (HC-MC) more strongly preferred the HC task. Participants experiencing stronger control were more likely to select the HC task in case of equal offers (Spearman's rho = 0.28, one-sided p = 0.048), were willing to forgo money in order to play the HC task (Spearman's rho = 0.26, one-sided p = 0.048), and showed shifts in the POE so that MC offers needed to be larger in order to achieve similar probabilities of selecting HC and MC (Spearman's rho = −0.24, one-sided p = 0.048, all p-values FDR-corrected; see Supplementary Table 7).…”
Section: Resultssupporting
confidence: 91%
“…Participants experiencing stronger control were more likely to select the HC task in case of equal offers (Spearman's rho = 0.28, one-sided p = 0.048), were willing to forgo money in order to play the HC task (Spearman's rho = 0.26, one-sided p = 0.048), and showed shifts in the POE so that MC offers needed to be larger in order to achieve similar probabilities of selecting HC and MC (Spearman's rho = −0.24, one-sided p = 0.048, all p-values FDR-corrected; see Supplementary Table 7). Collectively, these findings support and extend previous studies that showed that mere choice is preferable to not having choices 18,55 by highlighting the notion of instrumental control over the outcomes for building preferences 23 , and emphasizing that self-related positive affect might be a relevant factor for mediating motivated behavior 25 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In line with these findings, it has been shown that in the Stroop task a cue indicating high efficacy improves behavioral performance (Dean Wolf, Cory, & Shenhav, 2018). At the neural level it has been shown that higher perceived efficacy increases the value of outcomes (Wang & Delgado, 2019) and strengthens their representation in the brain network including the striatum, prefrontal and parietal cortex (Wisniewski, Forstmann, & Brass, 2019). While there is initial evidence to support the role of efficacy in the allocation of cognitive effort, the neural dynamics through which efficacy estimates are formed and the way in which they influence the allocation of cognitive control remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has largely implicated the ventromedial prefrontal cortex (vmPFC; Amat et al, 2005 ; Christianson et al, 2009 ) and the striatum ( Leotti and Delgado, 2011 , 2014 ) as critical regions associated with perceiving a sense of control. The vmPFC in particular, is important in encoding the subjective value of perceived control—how much people prefer to exert vs. give up control in order to attain a reward ( Wang and Delgado, 2019 ). As such, we hypothesize that perceived control can not only engender avoidance behavior changes via its protective effects, it is likely that the vmPFC is involved in mediating such behavioral changes.…”
Section: Introductionmentioning
confidence: 99%